The Production of Safe Wooden Play Equipment for Early Childhood: A Case Study of CV Baja Toys - Maknun, Lu'lu'il; Rohimah, Umi Nafisatur; Nuraziza, Saskia Ramona; Safitri, Lailatul Fadzilah; Hakim, Rahman (THUFULA, 2025)
The purpose of this study is to analyse the process of creating educational play equipment (APE) made of wood at CV Baja Toys. This study uses a descriptive qualitative method with a case study approach to examine information about the design, materials, and stages of production of safe and childhood-shaped APE. CV Baja Toys produces indoor and outdoor APE, mainly from wood such as pine and mahogany, as well as small iron components for outdoor toys. APE is made in six stages. In other words, cutting, causing, refining, painting, assembly, and packaging. Each phase is carefully considered to ensure product safety, including adjusting component sizes to prevent risk to children. This study also identified obstacles to the production process, such as weather conditions, which can impact product quality. The results of the study indicate that the APE produced by CV Baja Toys meets the safety, durability, and educational standards necessary for the growth and development of children. Thus, the APE produced is an effective way to support the learning process of Kindergarten/Early Childhood Education.